SIMULASI AUDIT DOSIMETRI TREATMENT PLANNING SYSTEM FOTON SINAR-X 6 MV MULTICENTER RADIOTERAPI - Suwandi, Suwandi; Wibowo, Wahyu Edy; Pawiro, Supriyanto Ardjo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
TPS is an important modality determining radiotherapy outcome. According to accident and incident international reporting database in radiotherapy, TPS related occurences are among the main sources of errors. TPS requires input beam data obtained through commissioning. The errors at this step results in systematic errors. The purpose of this study is to verify TPS dosimetric to determine the deviation between the dose calculated by TPS and measured dose in phantom representing the dose received tumor targets. This study using CIRS phantom 002LFC representing the human thorax and simulates the whole chain of external beam radiotherapy activities. The phantom was scanned using CT Scanner and eight test cases were planned on TPS, was tested in four centers of radiotherapy. The dose were measured using 0.6 cm3 ionization chambers. Measured and TPS calculated doses were compared. The results of this study showed that most of the deviation are within tolerance. The deviations out of the tolerance found in most of the test cases at center radiotherapy 2. Conclusions of this study is generally, the TPS used for radiotherapy treatment planning at the four centers are good in accuracy, except TPS at center 2, most of the deviation out of tolerance. Keywords: Dosimetric audit, TPS, point dose, deviation, tumor target.